SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI PEMASARAN LAPTOP BEKAS MENGGUNAKAN METODE ARAS - Purba, Mila Hanim; Sihombing, Volvo; Irmayani, Deci (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This study aims to develop a decision support system (DSS) based on the Additive Ratio Assessment (ARAS) method to help used laptop entrepreneurs in Bagan Sinembah District in determining the optimal marketing location. The problems faced include the selection of business locations that are often done based on intuition without considering data and strategic factors, such as market demand, operational costs, infrastructure, market competition, and economic growth potential. The research method involves identifying the main criteria, collecting alternative location data, normalizing data using the ARAS method, and calculating the utility value for each alternative. The results of the study showed that the three best alternatives for marketing locations were A1 in the first position with a utility value of 0.86507, A4 in the second position with a value of 0.79749, and A6 in the third position with a value of 0.78166. Based on the results of the study, it shows that the ARAS method is effective in dealing with multi-criteria problems, providing recommendations for marketing locations with the highest utility value, which is considered the best choice.